PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, DAN KAPABILITAS TEKNIK TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI - Dean Ariel (2022)
This research is a quantitative research that examines the effect of system quality, information quality, and technical capability on information system user satisfaction using the Technology Acceptance Model (TAM) theory. This study uses a population of users of accounting information system software at several MSMEs in South Jakarta. Hypothesis testing was carried out with multiple linear analysis by looking at the direct and indirect effects related to each independent variable on the dependent variable using the SPSS tool with a significance level of 5% (0.05). The results of the test obtained (1) the quality of the system has a positive and significant effect on user satisfaction, (2) the quality of information has a positive and significant influence on user satisfaction, and (3) technical capability has a positive and significant influence on user satisfaction.